Identifikasi Infeksi Cendawan Patogen pada Jagung Pipil dalam Penyimpanan Suhu Ruang - Nofiyanti, Sri Handayani; Ahmad, Usman; Tondok, Efi Toding (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2021)
Postharvest handling of shelled corn often faces problems caused by fungal attacks during storage, resulting deterioration due to physical and biological damages. This study aimed to identify various pathogenic fungi that infected shelled corn during storage through the characteristics and growth phases of each fungus as well as to find out the interaction between fungi and shelled corn based on the different parts of kernel structure infected by the fungus. The blotter test method (ISTA) was used to isolate the fungal pathogens from infected shelled corn then purified and cultivated on PDA. Subsequent, microscopic and macroscopic observations were made by capturing images for eight days. Observations showed that Aspergillus spp predominantly infected the pericarp of the shelled corn (61%), Penicillium sp (15%) tended to infect the tip cap, Talaromyces sp (13%) on the endosperm, and Rhizopus sp (11%) on the germ. The largest colony areas after 8-day incubation were Rhizopus sp, followed by Aspergillus spp, Talaromyces sp, and Peniillium sp. The fungus growth phase had a logarithmic pattern with different time for each stage. Therefore, this pattern can be used as a reference for proper preventing time in shelled corn storage before the fungi can produce mycotoxins in the stationary phase and also the possibility to use the fungi as biological agents, such as antibiosis, competition, or parasite.